GENDER IN FINANCIAL LITERACY: AN ANALYSIS OF ECONOMIC EMPOWERMENT - Ade Maharini Adiandari (Journal of Social and Economics Research, 2023)
In this comprehensive study, we explored the intricate relationship between gender, financial literacy, and its impact on economic empowerment. The research was conducted to understand better the disparities in financial knowledge between genders and their consequences on economic well-being. The study involved quantitative and qualitative data collection methods, allowing for a holistic examination of the subject matter. Key findings of this research indicated significant gender-based differences in financial literacy, with a 12% gap observed, favoring one gender. These disparities have wide-reaching implications for economic empowerment, as they contribute to income disparities and financial decision-making. Societal expectations and cultural norms emerged as influential factors, shaping financial behaviors and attitudes differently for each gender. Addressing these disparities is crucial for advancing gender equality and promoting economic independence among women. Tailored financial education programs considering gender-specific needs and challenges are essential in bridging the financial literacy gap. Broader financial education initiatives targeting both genders can further enhance financial knowledge and empower individuals to make informed financial decisions. The implications of this study extend beyond financial literacy, underscoring the importance of achieving gender equality in financial decision-making to promote gender equity and enhance women's economic well-being. Policymakers, educators, and researchers can draw valuable insights from this research to inform policy recommendations and initiatives to break down gender-based financial disparities.